Economic Dependency on Work: A Moderator of the Relationship Between Organizational Commitment and Performance - Brett, Joan F.; Cron, William L.; Slocum, John W. (Academy of Management Journal, 1995)
This study examined the role of employees' financial requirements as a moderator of the relationship between their organizational commitment and performance. Hypotheses were tested on two samples of salespeople from different organizations. The results of hierarchical regression analysis indicated stronger relationships between organizational commitment and performance for those with low financial requirements than for those with high requirements.